Solvent Polarity and Temperature Effects on Extracted Secondary Metabolite from the Fruit of Tetrapleura Tetraptera and its Antibacterial Potential on Uropathogens (Global Journal of Medical Research, 2022)
Odoriferous medicinal plants are known to be used as natural therapeutic agents, as they are rich sources of terpenoids and polyphenols. This study was aimed at evaluating the solvent polarity, temperature effects and synergistic potential of the phytochemicals in the fruit extract obtained from the fruit of Tetrapleura tetraptera on clinically isolated uropathogens. T. tetraptera has being used locally in treating some ailments. The sample was extracted using methanol, hot water and cold water respectively. The quantitative and qualitative compositional analysis of the secondary metabolites of the fruit extract was carried out using Gas chromatography-mass spectrometry (GC-MS). The antibacterial screening was carried out using agar-well diffusion assay. The GC-MS analysis of the fruit extract led to the identification of thirtyfive (35) constituents amounting to 96.28% of the extract.
Keywords: tetrapleura tetraptera; fruit extract; phytochemical; pathogen; natural antibiotic